2005
DOI: 10.1063/1.2139673
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of torsion on O–H stretch overtone spectra and direct overtone photolysis of methyl hydroperoxide

Abstract: We use laser photoacoustic spectroscopy to obtain overtone spectra at three through six quanta of O-H stretch excitation (3nu(OH)-6nu(OH)) for methyl hydroperoxide (MeOOH). Extending the spectral regions beyond our previous work reveals new features that can be attributed to transitions involving torsion about the O-O bond. Experimental spectral profiles (3nu(OH)-6nu(OH)) and cross sections (3nu(OH)-5nu(OH)) at room temperature show a good agreement with the simulated spectra that we obtain from ab initio calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…As has been demonstrated, the accuracy of the RCCSD(T)-F12 harmonic fundamentals is of the same order of magnitude than those determined with RCCSD(T) and a complete basis set. 39,40 To our knowledge, there are no previous experimental data to be compared with our results with the exception of the OH-stretching fundamental of MeOOH predicted to lie at ν 1 = 3679 cm −1 (ω = 3773 ± 15 cm −1 ; anharmonicity = 94 ± 3 cm −1 ) by Haynes et al (2005). 3 The theoretical value of ν 1 = 3610 cm −1 (ω = 3797 cm −1 ; anharmonicity = 187 cm −1 ) is in a very good agreement with the experimental one.…”
Section: Full-dimensional Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…As has been demonstrated, the accuracy of the RCCSD(T)-F12 harmonic fundamentals is of the same order of magnitude than those determined with RCCSD(T) and a complete basis set. 39,40 To our knowledge, there are no previous experimental data to be compared with our results with the exception of the OH-stretching fundamental of MeOOH predicted to lie at ν 1 = 3679 cm −1 (ω = 3773 ± 15 cm −1 ; anharmonicity = 94 ± 3 cm −1 ) by Haynes et al (2005). 3 The theoretical value of ν 1 = 3610 cm −1 (ω = 3797 cm −1 ; anharmonicity = 187 cm −1 ) is in a very good agreement with the experimental one.…”
Section: Full-dimensional Analysismentioning
confidence: 61%
“…2 Its contribution to the atmospheric oxidizing capacity has motivated previous collisional and spectroscopic studies devoted to the photofragmentation processes and to the measurement and analysis of the infrared spectra in the Nν OH (N = 2,6) regions. [3][4][5][6] The main source of MeOOH in the earth atmosphere is the combination of HO 2 and CH 3 O 2 radicals. 1 It has not been discovered in gas phase extraterrestrial sources and planetary atmospheres but it represents a good candidate to be detected with the new radioastronomical observatories.…”
Section: Introductionmentioning
confidence: 99%
“…Slight differences in the product distribution of OH were seen when the combination band of the O-H stretch overtone and the torsion mode was excited compared to the excitation via pure O-H stretch overtone. Following their work, overtone-induced photodissociation reactions have been investigated in several molecules with the O-O-H bond, such as peroxynitric acid (O 2 NOOH) [28,32], peroxynitrous acid (ONOOH) [20,[64][65][66], methyl hydroperoxide (CH 3 OOH) [27,67], as well as hydrogen trioxy radical (OOOH) [68,69]. Furthermore, systems with weak bonds adjacent to the O-H bond, such as N-O (De∼55 kcal/mol) in nitric acid (O 2 NOH) [70,71] and O-Cl (De∼43 kcal) in ClOH [72][73][74][75], have also been investigated as possible candidates to dissociate following O-H stretching overtone excitation.…”
Section: Vibrationally Excited Statesmentioning
confidence: 99%
“…It has recently been shown that these ground electronic state photoreactions can be important in the atmosphere when excited electronic state reactions are precluded by the lack of appropriate electronic states accessible in the solar spectrum [7][8][9][10][11][12][13][14][15][16]. Atmospheric conditions, where UV photons are suppressed as is the case at high zenith angle which occurs at dusk, dawn, or the edge of a polar vortex, are also auspicious for such ground state photochemistry [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Atmospheric chemists describe the rate of formation of photoproducts from atmospheric processing as a first-order rate constant J (J-values), where J is given by a convolution of the photoabsorption cross-section, the wavenumber dependent photochemical quantum yield, and the photon flux of solar radiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we were unable to find literature data on experimental IR and Raman spectra in the low-frequency spectral range (10 -500 cm -1 ). At the same time, the spectral region, in which the overtones of the stretching vibrations of the hydroxyl group (6000 -19 500 cm -1 ) appear, has been studied experimentally and theoretically in great detail [13][14][15][16][17]. These studies showed the existence of a significant interaction of stretching and torsional vibrations of the hydroxyl group.…”
Section: Introductionmentioning
confidence: 99%